Supplementation of suckling beef calves with different levels of crude protein on tropical pasture - Lopes, Sidnei Antonio; Paulino, Mário Fonseca; Detmann, Edenio; Valadares Filho, Sebastião de Campos; Barros, Lívia Vieira; Cardenas, Javier Enrique Garces; Almeida, Daniel Mageste; Martins, Leandro Soares; Silva, Aline Gomes; Valente, Ériton Egídio Lisboa (Tropical Animal Health and Production, 2013)
The effects of supplementation with different levels of crude protein on performance, intake and nutrient digestibility and efficiency of microbial protein synthesis in suckling beef calves on pasture were assessed. Fifty-five calves, with an average age of 100 days and an initial average body weight of 110 ± 7.5 kg and their respective dams, were used. The experimental design was completely randomised with five treatments and 11 replications. The experimental treatments for calves were as follows: control = calves received only mineral mixture; supplementation levels = calves received supplement containing 8, 19, 30 or 41 % of crude protein (CP, at a rate of 0.5 % of body weight (BW)). The cows received only mineral mixture ad libitum. Supplemented calves had higher (P < 0.1) average daily gain (ADG). Protein levels showed a quadratic effect (P < 0.1) on average daily gain (ADG) of calves. There was no difference in total dry matter (DM) intake (P > 0.1). However, intake of dry matter forage (DMF) presented cubic profiles (P < 0.1), with CP levels in the supplements. Supplementation increased (P < 0.1) the digestibility of nutrients, except for the digestibility of neutral detergent fibre. Supplementation increased (P < 0.1) the production of microbial nitrogen and N losses in urine. It can be concluded that multiple supplementations optimise the performance of beef calves on creep feeding. The intake of supplements with CP levels between 8 and 30 % partially replaces of the pasture ingested by calves and increases the digestibility of the diet.
Keywords: Calves; Creep feeding; Digestibility; Intake; Nellore; Supplementation